Livelihood Strategy of Bote Community: A Case Study of Bote Community of Patihani VDC of Chitwan - Acharya, Umesh Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2011)
This paper discusses upon the changes of Bote community of Nepal, in case of Patihani V.D.C. These changes are influenced by process of urbanization, globalization which has created constraints and opportunities on "Bote people of Patihani VDC". Historically these people had their livelihood from agriculture. Land was a major household asset and crop production (maize, millet, paddy, wheat etc.) was the means of survival. But the rapid process of urbanization and globalization has pushed them in transition both with opportunities as well as constraints. The household assets have undergone rapid modification. Now they have no option other than modifying the traditional occupation. Land fragmentation and change in social institution are resulted from the urbanization and globalization. The livelihood diversification and foreign employment have recently emerged as how livelihood strategies in the study area. Due to the proximity to the market, the influence of the urbanization is more apparent in the Bote Village. Most of the households follow the multiple occupations besides agriculture. The role of agriculture activities in their life is substantial. Although a few households sell their crops however most of them sell vegetables. The livelihood strategy of Bote community in the study area is in transition. It is shifted from agriculture to non-agricultural one. It is necessary to ensure access to resources and increase social and political participation of Bote community for integral development of rural community in Nepal. Keywords: poverty; urbanization; commercial farming; tarai ethnic group; traditional occupation DOI: 10.3126/dsaj.v4i0.4524 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.247-260